2011
DOI: 10.2166/wst.2011.237
|View full text |Cite
|
Sign up to set email alerts
|

Influence of natural organic matter on equilibrium adsorption of neutral and charged pharmaceuticals onto activated carbon

Abstract: Natural organic matter (NOM) can influence pharmaceutical adsorption onto granular activated carbon (GAC) by direct adsorption competition and pore blocking. However, in the literature there is limited information on which of these mechanisms is more important and how this is related to NOM and pharmaceutical properties. Adsorption batch experiments were carried out in ultrapure, waste- and surface water and fresh and NOM preloaded GAC was used. Twenty-one pharmaceuticals were selected with varying hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(42 citation statements)
references
References 20 publications
(31 reference statements)
3
38
0
1
Order By: Relevance
“…This effect may be enhanced for SPAC and due to a greater number of large molecules at the surface of SPAC. Moreover, as observed previously (de Ridder et al, 2011), increased adsorption of negatively charged organic matter on the surface of the carbon particles can lead to a more negatively charged surface. The increased EfOM loading on SPAC could consequently increase electrostatic repulsion of anionic pharmaceuticals such as sulfamethoxazole.…”
Section: Influence Of Effluent Organic Mattersupporting
confidence: 67%
See 1 more Smart Citation
“…This effect may be enhanced for SPAC and due to a greater number of large molecules at the surface of SPAC. Moreover, as observed previously (de Ridder et al, 2011), increased adsorption of negatively charged organic matter on the surface of the carbon particles can lead to a more negatively charged surface. The increased EfOM loading on SPAC could consequently increase electrostatic repulsion of anionic pharmaceuticals such as sulfamethoxazole.…”
Section: Influence Of Effluent Organic Mattersupporting
confidence: 67%
“…3), suggesting adverse effects of competing wastewater matrix components on the adsorption of target micropollutant. It is largely acknowledged that background organic matter reduces the number of adsorption sites available for micropollutants, either through direct competition for adsorption sites and/or pore blocking, and consequently decreases the adsorption efficiency of PAC (de Ridder et al, 2011;Delgado et al, 2012;Kovalova et al, 2013a;Mailler et al, 2014;Margot et al, 2013). This effect is well illustrated in Fig.…”
Section: Adsorption Equilibrium In Wastewatermentioning
confidence: 84%
“…It was argued that the adsorbed EfOM would lower the net surface pH to negative of the otherwise neutral or slightly positively charged PAC [94], thereby attracting the positively charged compounds and repulsing the negatively charged compounds. The compounds with medium affinity to PAC, showing 70-90% removal, were predominantly negatively charged substances with hydrophobic properties (e.g., acidic lipid regulators and analgesic and anti-inflammatories, log D ow 1.7-3.4, Table 2) indicating that the electrostatic repulsion could be offset by hydrophobic partitioning, though other mechanisms also contribute to the attraction [93]. It has been reported that for compounds with log D ow > 3.7, hydrophobic partitioning is the dominating mechanism leading to PAC adsorption [93], which explains high removal (>90%), for instance, for mefenamic acid (log D ow 5.12).…”
Section: Adsorption Processes (Gac and Pac)mentioning
confidence: 99%
“…The compounds with medium affinity to PAC, showing 70-90% removal, were predominantly negatively charged substances with hydrophobic properties (e.g., acidic lipid regulators and analgesic and anti-inflammatories, log D ow 1.7-3.4, Table 2) indicating that the electrostatic repulsion could be offset by hydrophobic partitioning, though other mechanisms also contribute to the attraction [93]. It has been reported that for compounds with log D ow > 3.7, hydrophobic partitioning is the dominating mechanism leading to PAC adsorption [93], which explains high removal (>90%), for instance, for mefenamic acid (log D ow 5.12). The somewhat unexpected poor removal (70-90%) of the 276 Persistent Organic Pollutants positively charged azithromycin (log D ow 2.8) was suggested to be caused by exclusion in the micropores of the PAC due to its large size [82].…”
Section: Adsorption Processes (Gac and Pac)mentioning
confidence: 99%
“…The second aspect was in the focus of this study. Activated carbon adsorption of OMP can be strongly deteriorated by the adsorption of EfOM (Yu et al, 2012;Zietzschmann et al, 2014bZietzschmann et al, , 2014c or natural organic matter (de Ridder et al, 2011;Matsui et al, 2003;Ternes et al, 2002). The competition mechanisms are direct competition for adsorption sites on the activated carbon internal surface, and blockage of activated carbon pores with larger molecules of the EfOM bulk organics .…”
Section: Introductionmentioning
confidence: 99%